Holistic Learning for Micro, Small and Medium Enterprises (MSMEs) Development Program - Salix Fini Maris (West Science Business and Management, 2024)
The focus of training is usually on specific skills that are needed today. Meanwhile, holistic learners tend to aim to achieve the highest level of knowledge awareness and appreciate the benefits it provides for their lives [1]. A holistic learning process is needed to identify all components that influence student development. Small and medium enterprises (MSMEs) are the subject of holistic learning because they have an economic potential that is of concern to always develop. The research approach is carried out through literature mapping, focusing on visual synthesis of the data collected and is an observation based on questions. Learning involves the learning model that best suits students, which focuses on learning through experience captured by kinesthetic memory. Holistic does not only focus on technical skills but also pays attention to internal motivation for achieving these skills. The existence of interaction not only increases the accumulation of knowledge but also a sense of mutual belonging to bear the same burden in successful learning. The next aspect is transformation which involves tools and facilities that support the change process, such as the use of information systems that facilitate collaboration and data analysis for learning evaluation. Holistic learning approach, MSMEs can develop their businesses in a way that is not only financially profitable, but also socially, environmentally and economically sustainable.